(untitled) (International journal of artificial intelligence, 2024)
The efficiency of banking activities holds significant importance in the modern economy. Banks provide financial services, attract capital, and contribute to the stable development of the economy. This article discusses the key elements of banking efficiency, ways to enhance it, and the existing challenges.